2010
DOI: 10.1007/s10895-009-0594-4
|View full text |Cite
|
Sign up to set email alerts
|

Water Stress Response of Conventional and Transgenic Soybean Plants Monitored by Chlorophyll a Fluorescence

Abstract: Two soybean cultivars, one conventional and a glyphosate-tolerant (transgenic), were submitted to the water stress and the chlorophyll a fluorescence induced by UV light was monitored daily during 16 days. In this work, 40 pots in total, 20 per cultivar were used in the investigation. Each cultivar was divided in two groups, the control group and the group submitted to the water stress. The stress response of the cultivars was monitored by red to far-red fluorescence ratio. The data indicate that the water str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
2
8
0
2
Order By: Relevance
“…For these authors, electron transfer is a dominant process when one considers the differences in chlorophylls' oxidation potential. Nanoparticles of gold are capable of interfering in electron dissipation processes in PSII (Caires et al, 2010), similarly, aluminum nanoparticles are able to induce toxic effects related to interaction between the particles and the surface active sites on the cell wall (Sadiq et al, 2011) but these ANPs are infinitely larger compared with ions. Some stress responses are related to Al 3+ ions released from ANPs in the medium playing a predominant role on cytotoxicity (Pakrashi et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…For these authors, electron transfer is a dominant process when one considers the differences in chlorophylls' oxidation potential. Nanoparticles of gold are capable of interfering in electron dissipation processes in PSII (Caires et al, 2010), similarly, aluminum nanoparticles are able to induce toxic effects related to interaction between the particles and the surface active sites on the cell wall (Sadiq et al, 2011) but these ANPs are infinitely larger compared with ions. Some stress responses are related to Al 3+ ions released from ANPs in the medium playing a predominant role on cytotoxicity (Pakrashi et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The chlorophyll a and total chlorophyll levels were altered, whereas chlorophyll b (accessory pigment) did not vary with Si addition. Photosynthetic pigments are highly responsible for photosynthetic metabolism in plants; chlorophyll a is the main agent responsible for allowing this interaction between the capture of solar energy and the process initiated within the chloroplasts, whereas chlorophyll b acts as an accessory pigment in the process of electron transfer to chlorophyll a (Caires et al, 2010;Bohr and Malik, 2011).…”
Section: Production Of Photosynthetic Pigmentsmentioning
confidence: 99%
“…In fact, most environmental stresses are expected to slowly modify the chlorophyll concentration [6]. In a recent report, our group showed that the F 685 /F 735 can be used to detect water stress in soybean plants and to distinguish transgenic from conventional plants [28].…”
Section: In Vivo Analysismentioning
confidence: 99%